I speak fast when I move fast: the speed of illusory self-motion (vection) modulates the speed of utterances - Seno, Takeharu; Ihaya, Keiko; Yamada, Yuki (Frontiers in Psychology, 2013)
Speed of utterance is an important factor in smooth and efficient conversation. We report a technique to increase utterance speed and that might improve a speaker's impression and information efficiency in conversation. We used a visual display consisting of optic flows in a large visual field that induced participants' illusory self-motion perception (vection). The speed of vection corresponded to the speed of the optic flows. Using this method, we investigated whether vection speed affects utterance speed. We presented fast- and slow-moving optic flow stimuli while dynamically swapping random dots presented to participants, during which time the participants were asked to talk for 2 min. Results revealed that the utterance speed was significantly faster in the fast optic flow condition. Our method could be a stepping stone for establishing a technique of modulating speech speed effectively.